Conversational expressions of emotions - Rutkowski, Mariusz (Papers in Linguistics, 2019)
The paper presents an analysis and interpretation of expressions of emotions in conversation. Interlocutors` emotional involvement is only fully observable in the context of other exchanges and patterns of behaviour of participants in a speech event. A framework which enables such a complete observation is the methodology of conversational analysis, which is based on detailed transcripts of authentic conversations. The paper presents an interpretation of an institutional interaction and an emergency phone call. In both interaction types some expressions of emotions were revealed and analysed in greater detail. The examined emotions were expressed by intonation, tone of the voice, louder articulation, interruptions, overlaps, and conflicting conversation scripts. In addition, the analysis demonstrates how preference organization in a conversation affects interlocutors` emotional behaviour, showing that dispreferred responses evoke emotional behaviour.